Evaluation of soybean genotypes for field resistance to stink bugs in Nigeria - Jackai, L.E.N.; Dashiell, K.E.; Bello, L.L. (1988)
A number of soybean breeding lines and other genotypes were screened for resistance to stink bugs under field conditions at two locations (Mokwa and Ibadan) in Nigeria using two dates of planting (DOP) and no insecticides for 2 years. Stink bug populations were high during the first year and moderate the second year. Bug damage to pods was scored in the field and seed damage assessed in the laboratory using plant samples obtained from the field. Overall, damage was greater in Mokwa than in Ibadan. Visual damage scores ranged from 4·0 to 9·0 (scale 1–9) during the first DOP in the first year at Mokwa and 2–6 during the second DOP. During the second year, damage scores ranged from an average of 3·8 to 4·9 for both DOPs. Seed damage ranged from an average of 32% to 59%. Visual damage scores were negatively correlated with yield, such that lower yields were obtained where higher scores were given. Our results show that pod and seed damage was often greater in the upper portion of the plant in the varieties tested, thus indicating where the feeding activity of the insects was concentrated. A seed damage ratio (SDR) is computed and used, among other parameters, to select TGx 713-09D, TGx 307-048D, TGx 306-036C and TGx 814-036D as the genotypes manifesting the highest level of field resistance. These results are discussed in relation to the development of soybean varieties resistant to stink bugs.